Preferences of lambs offered Italian ryegrass (Lolium multiflorum L.) and barley (Hordeum vulgare L.) herbage as choices - Catanese, Francisco Hernan (2009)
Partial preference for feeds in ruminants is a welldocumented phenomenon although their explanation can be elusive. The hypothesis was tested that sheep offered herbage of two annual grass species differing in chemical composition free-choice would select a diet that would maximize the nutritive value of the diet compared with sheep offered each herbage separately through a greater nutrient balance and synchronization of nutrient release for efficient ruminal microbial function. Fifteen male lambs were placed into metabolic cages, and randomly assigned to three treatments (n = 5): Italian ryegrass fresh herbage (treatment R), barley fresh herbage (treatment B) or free-choice Italian ryegrass and barley fresh herbage (treatment RB). Both herbages had similar crude protein concentrations but Italian ryegrass herbage had higher concentration of water-soluble carbohydrates and lower concentration of fibre than barley herbage. Lambs were exposed to the treatments for 15 d. Lambs on treatment RB showed a partial preference of 0Æ82 (s.e. 0Æ031) for Italian ryegrass. Lambs on treatment RB had higher intakes of digestible dry matter and higher values for nitrogen retention than lambs on treatment B although similar to that of lambs on treatment R. The results for the dietary choices were not always consistent with maximizing the nutritive value of the diet. Other explanations, such as lambs needed to sample and track the nutritive value of dietary options or there was the development of transient food aversions, were also possible.